Investigating the association between sport motivation with general health in faculty members of Fars University of medical sciences (A cross sectional-analytical study in 2018) - Sobhanian, Saeed; Khoshnam, Ebrahim; Naderian, Masoud; Barhagh, Hosein Dast (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Motivation is one of the main indices in many theories of learning and psychology. Sports psychologists consider a variety of motivations, including the motivation for progress and achievement, the motivation for competition, the motivation for participation, etc. with specific concepts. Therefore, this study aimed to examine the association between sport motivations with general health in Fars University of medical sciences. This study was a cross sectional-analytical research. The research population consisted of faculty members of Fars University of medical sciences. Sampling was done randomly with a sample size of 244 people. Data were collected using demographic information, sport motivation questionnaire, and general health questionnaire. Descriptive statistics and analytical statistics were used to analyze the data using SPSS-16 software. The results of Pearson correlation test showed that there was a significant correlation between general health and sport motivation (P = 0.001, r = -0.252); among the components of sport motivation, only physical recovery dimensions, competition, weight control, and health do not have a significant correlation with the general health. The results of this study indicated an association between general health and sport motivation and some of its components in the study population. Therefore, the applying methods for increasing the athletic motivation to achieve the desired levels of general health and its components by modeling the results can be useful for planners and managers of human resources in universities.